Advances in nanophotonics - Gong, Qihuang; Li, Zhi; Tong, Limin; Wang, Yipei; Wang, Yufei; Zheng, Wanhua (Advances in optical physics, 2018)
Presents recent developments in theoretical and experimental research of nanophotonics. Discusses properties and features of nanophotonic devices, e.g. scanning near-field optical microscopy, nanofiber/nanowire based photonic devices. Illustrates the most promising nanophotonic devices and instruments and their application. Suits well for researchers and graduates in nanophotonics field. Contents: Scanning near-field optical microscopy; Nanofibers/nanowires and their applications in photonic components and devices; Micro/nano-optoelectronic devices based on photonic crystal.